2017
DOI: 10.1186/s12904-017-0218-8
|View full text |Cite|
|
Sign up to set email alerts
|

Social workers’ involvement in advance care planning: a systematic narrative review

Abstract: BackgroundAdvance care planning is a process of discussion that enables competent adults to express their wishes about end-of-life care through periods of decisional incapacity. Although a number of studies have documented social workers’ attitudes toward, knowledge about, and involvement in advance care planning, the information is fragmented. The purpose of this review was to provide a narrative synthesis of evidence on social workers’ perspectives and experiences regarding implementation of advance care pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 52 publications
2
37
1
1
Order By: Relevance
“…Specifically, in the case of patients with cancer or organ failure, quick access to palliative care beds must be available and preferences regarding place of death must be taken into consideration. Our results also show that the role of the social worker on these teams and their integration in the social and community network must be reinforced [57][58][59][60][61][62][63] and that, due to the intensity of this type of care (refractoriness, changing circumstances and short duration), health-care teams and professionals must be encouraged to practice self-care. [64][65][66][67][68] These findings highlight the importance of the presence of a skilled caregiver in the home, as well as the need for assessment of all areas included in the model due to the heavy burden that the psychosocial field can have on suffering at the end-of-life.…”
Section: Generalizations and Perspectivesmentioning
confidence: 99%
“…Specifically, in the case of patients with cancer or organ failure, quick access to palliative care beds must be available and preferences regarding place of death must be taken into consideration. Our results also show that the role of the social worker on these teams and their integration in the social and community network must be reinforced [57][58][59][60][61][62][63] and that, due to the intensity of this type of care (refractoriness, changing circumstances and short duration), health-care teams and professionals must be encouraged to practice self-care. [64][65][66][67][68] These findings highlight the importance of the presence of a skilled caregiver in the home, as well as the need for assessment of all areas included in the model due to the heavy burden that the psychosocial field can have on suffering at the end-of-life.…”
Section: Generalizations and Perspectivesmentioning
confidence: 99%
“…A systematic review of social workers' ACP responsibilities identified a number of duties, including initiating discussions, advocating for patients' rights, providing patient or family education or counseling, facilitating communication, conflict resolution, and documentation. 15 The team nurse can provide ongoing medical monitoring, evaluate treatment effectiveness, and instruct patients about treatments and medications. The chaplain is charged with addressing the spiritual implications and significance of the prognosis and with meeting patients' spiritual needs.…”
Section: It Takes a Teammentioning
confidence: 99%
“…2 As noted in a recent systematic review, social workers generally consider being a part of ACP discussions as an integral part of their role. 3 According to the National Association of Social Work Standards for Palliative and End-of-Life Care, 4 a social worker's full scope of practice includes advocacy of client/ client system choices, preferences, values, and beliefs in palliative and EOL care. Because a tenet of social work practice is building a therapeutic relationship, PSWs work hard to earn the trust and respect of patients, who then feel more comfortable sharing intimate details about values and goals.…”
Section: Introductionmentioning
confidence: 99%
“…Hospice social workers and community-based PSWs were found to increase advance directive (AD) documentation rates more than hospital-based HSW in part due to strong interdisciplinary dynamics within hospice and palliative settings. 5 Additionally, HSW introduce ACP more frequently and spend 30-60 minutes per day on the topic, 3 as compared with physicians and nurses who spend, on average, <30 minutes in these discussions. 3,6 Despite this discrepancy, HSW still feel this time is inadequate given the nuances of these conversations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation